THE IMPORTANCE OF NURSING WORK IN STUDYING JAW ANATOMY (Modern education and development, 2024)
The study of jaw anatomy is essential for understanding the functions, health, and diseases of the jaw and related structures. Nurses play a significant role in the clinical and educational aspects of jaw anatomy, contributing to patient care, early diagnosis, and post-treatment management. This article explores the crucial role of nursing professionals in the study of jaw anatomy, emphasizing their contribution to clinical practice, patient education, and multidisciplinary care in dental and medical settings.